Pengaruh Beban Kerja dan Stres Kerja terhadap Produktivitas Karyawan yang Bekerja Work From Home (WFH) dalam Situasi Covid-19 - Wina Widia; sri suwarsi (UNISBA Press, 2022)
This research was conducted on employees of the Food Security Service of Subang Regency. After the authors conducted a pre-survey by distributing questionnaires and interviews about workload and work stress on employee productivity, the results of the interviews concluded that employees felt that there was a time limit or deadline, work demands, dual roles and role conflicts, looking for news about Covid-19 that excessive workload, repetition of motion, responsibility when WFH against others creates pressure resulting in employees experiencing excessive workloads, and changes in the work environment, task demands, lack of support from groups, lack of personality maturity and self-control can result in employees experiencing stress at work will result in reduced productivity at work. This study uses descriptive and verification methods, using a quantitative approach and operating calculations using the IBMSPSS 25.0 program. This study aims to determine whether there is an influence between workload and work stress on the productivity of employees who work from Home (WFH) in the Covid 19 situation at the Food Security Service of Subang Regency. Collecting data obtained through questionnaires, observations, interviews, and literature studies. The sampling technique is saturated sampling. Respondents in this study were employees of the Food Security Service of Subang Regency, amounting to 41 people. The results of this study conclude that: 1) Workload at the Food Security Service in Subang Regency is in the Very High category 2) Work Stress at the Food Security Office in Subang Regency is in the Very High category 3) Employee Productivity at the Food Security Office in Subang Regency is in the Low category. 4) Workload (X1) partially has a significant effect on Employee Productivity (Y). 5) Work Stress (X2) partially has a significant effect on Employee Productivity (Y). 6) Workload (X1) and Work Stress (X2) simultaneously have a significant effect on Employee Productivity (Y). Keywords: Workload, Work Stress, Employee Productivity, WFH, Covid-19 Penelitian ini dilakukan kepada para pegawai Dinas Ketahanan Pangan Kabupaten Subang. Setelah penulis melakukan pra survey dengan menyebarkan kuisioner dan wawancara tentang beban kerja dan stres kerja terhadap produktivitas karyawan, hasil kuisioner dapat disimpulkan bahwa pegawai merasa adanya ketentuan batas waktu atau deadline, tuntutan kerja, kemenduaan peran dan konflik peran, mencari berita mengenai Covid-19 yang berlebihan, pengulangan gerak, tanggung jawab ketika WFH terhadap orang lain menimbulkan tekanan sehingga mengakibatkan pegawai mengalami beban kerja berlebih, dan perubahan lingkungan kerja, tuntutan tugas, kurangnya dukungan dari kelompok, kurangnya kematangan kepribadian dan pengendalian diri dapat mengakibatkan pegawai megalami stres dalam bekerja akan mengakibatkan berkurangnya produktivitas dalam bekerja. Penelitian ini menggunakan metode deskriptif dan verifikatif, dengan menggunakan pendekatan kuantitatif dan mengoprasikan perhitungan menggunakan program IBMSPSS 25.0. Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh antara beban kerja dan stres kerja terhadap produktivitas karyawan yang bekerja Work From Home (WFH) dalam situasi Covid 19 pada Dinas Ketahanan Pangan Kabupaten Subang. Pengumpulan data yang diperoleh melalui kuisioner, observasi, wawancara, dan studi pustaka. Teknik penarikan sampel adalah sampling jenuh. Responden dalam penelitian ini adalah pegawai Dinas Ketahanan Pangan Kabupaten Subang yang berjumlah 41 orang. Hasil penelitian ini menyimpulkan bahwa: 1) Beban Kerja pada Dinas Ketahanan Pangan Kabupaten Subang termasuk kategori Sangat Tinggi 2) Stres Kerja pada Dinas Ketahanan Pangan Kabupaten Subang termasuk kategori Sangat Tinggi 3) Produktivitas Karyawan pada Dinas Ketahanan Pangan Kabupaten Subang termasuk kategori Rendah. 4) Beban Kerja (X1) secara parsial berpengaruh signifikan terhadap Produktivitas Karyawan (Y). 5) Stres Kerja (X2) secara parsial berpengaruh signifikan terhadap Produktivitas Karyawan (Y). 6) Beban kerja (X1) dan Stres Kerja (X2) secara simultan berpengaruh signifikan terhadap Produktivitas Karyawan (Y). Kata kunci : Beban Kerja, Stres Kerja, Produktivitas Karyawan, WFH, Covid-19